Penggunaan Media Video Dan Lembar Balik Meningkatkan Perilaku Wanita Usia Subur Di Desa Penarukan Kerambitan Tabanan Dalam Melakukan Pemeriksaan Sadari Tahun 2018 - Ni Ketut Somoyani; Ni Luh Putu Sri Erawati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2019)
Breast cancer is a malignancy originating from the milk glands, glandular channels and supporting tissues of the breast. Cancer is the second highest cause of death in the world after cardiovascular disease. This study aims to determine the effectiveness of the use of video and flipsheets media on the behavior of reproductive women in conducting breast self-examination (BSE) in Penarukan Kerambitan Village, Tabanan. This study was included in Quasy-experimental with posttest only with control group design. The sample size is 43 respondents for each group who fit the inclusion criteria, using consecutive sampling. Respondents were divided into 3 groups, group one was given counseling with video media, the second group was given counseling with flip sheet, and the third group was only given counseling without media. The data’s knowledge was collected with questionnaires, for behavior using observation sheets. The results of the study based on data analysis used were One way ANOVA test results, found that there were significant mean differences between the three study groups determined from the value of p = 0.002. Followed by the Post Hoc test with p value = 0.001. The mean difference between the group that got the video and the control group was 8,177. Demonstration method with the use of BSE videos and flipsheets will increase knowledge compared to the lecture form method. The results in the control group were lower than in the video group, this is because some respondents said that technically the methods of BSE examination were not widely recognized